The methods of raising philanthropic funds in the management of non-governmental organization; determinants = Sposoby pozyskiwanie środków filantropijnych w zarządzaniu organizacją pozarządową; uwarunkowania - Stankiewicz, Janina; Seiler, Bartosz (Zielona Góra: Faculty of Economics and Management Press)
The article discusses the issues of obtaining financial resources by Polish non-governmental organizations, with particular emphasis on the philanthropic funds. The prevalence of the use of philanthropic resources by the analyzed entities was presented, as well as the determinants related to this process.
Keywords: organizacja pozarządowa; organizacja non-profit; fundraising; filantropia; non-governmental organization; non profit organization; philanthropy